Recruitment challenges in clinical research including cancer patients and caregivers. Issue 1 (December 2015) - Sygna, Karin; Johansen, Safora; Ruland, Cornelia
Abstract Background To test seven different strategies for recruitment in a randomized controlled trial, to report documented response data from each strategy, and to discuss recruitment challenges. Methods We used 5 opt-in (potential participants have to do something active to contact or be contacted by the researcher) and 2 opt-out (potential participants have the option to decline being contacted about a study) recruitment strategies from February 2013 until July 2014 to contact 1562 cancer patient candidates for participation in a randomized controlled trial. For each of these cancer patients a caregiver was also invited to take part in the study. Results Of the 1562 candidates, 22.6 % were ineligible on initial contact, 56.7 % declined to participate on initial contact, and 8.9 % agreed orally to participate but did not complete the enrollment. The 2 opt-out strategies, on-site recruitment and routine care letters recruitment, yielded the highest number of recruited participants with 79 dyads and 58 dyads respectively, constituting 42.7 % and 31.4 % of the total number of enrolled candidates. The 5 opt-in recruitment approaches yielded 49 dyads for the study. Almost half of these dyads were recruited using the approach termed "relying on providers at the hospital." Conclusions In this study, opt-out recruitment strategies appeared to be the most effective. Trial registration Registration numberNCT01867723, registered February 2012.